2010
DOI: 10.22621/cfn.v124i2.1051
|View full text |Cite
|
Sign up to set email alerts
|

Over-wintering Characteristics of West-Central Wisconsin Blanding's Turtles, <em>Emydoidea blandingii</em>

Abstract: Hibernation of adult-sized Blanding's Turtles was studied at two west-central Wisconsin sites between 1991 and 2008. Turtles arrived at hibernacula from mid September to early October, spending 126 to 216 days at these sites, and generally emerged in early April yearly. Sixty percent of females and 30 percent of males hibernated in natural over man-made structures as hibernation sites. Anoxic conditions near five hibernation sites ranged from 78 to 100 days. Shell temperatures of three turtles monitored over f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Both our juvenile cohorts initiated brumation from late October to early November, while emergence was observed from early to mid‐April. Ross and Anderson (1990) found Blanding's turtles in central Wisconsin, USA initiated brumation from 31 October to 15 November, whereas Newton and Herman (2009) and Thiel and Wilder (2010) both observed Blanding's turtles in Wisconsin and Nova Scotia, Canada, respectively, moving to their overwinter sites from September to mid‐November. Edge et al (2009) found that adult Blanding's turtles in Ontario, Canada emerged from brumation in mid‐April.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both our juvenile cohorts initiated brumation from late October to early November, while emergence was observed from early to mid‐April. Ross and Anderson (1990) found Blanding's turtles in central Wisconsin, USA initiated brumation from 31 October to 15 November, whereas Newton and Herman (2009) and Thiel and Wilder (2010) both observed Blanding's turtles in Wisconsin and Nova Scotia, Canada, respectively, moving to their overwinter sites from September to mid‐November. Edge et al (2009) found that adult Blanding's turtles in Ontario, Canada emerged from brumation in mid‐April.…”
Section: Discussionmentioning
confidence: 99%
“…non‐parametric method to measure the probability of occurrence based on the density of points in similar areas). Variation in seasonal movement areas estimates were calculated for each individual juvenile released during each season (Table 1), approximately following the phenology of Blanding's turtle activity in the adjacent state of Wisconsin, USA (Ross and Anderson 1990, Thiel and Wilder 2010), and for AHRs (i.e. total active season; static location of the juveniles during brumation were excluded from SMA and AHR calculations).…”
Section: Methodsmentioning
confidence: 99%